Sosialisasi dan Pelatihan Teknis Asesmen Nasional untuk Sekolah Dasar Rara - Karolus Wulla Rato; Sihang Gregorius Balimema; Herman Huki Ratu; Noviana Martha Dimu; Katarina Yunita Riti; Gergorius Kopong Pati; Paulino Lucky Puty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The Community Partnership Program (PKM) aims to improve the capacity of teachers at Rara Elementary School in understanding and implementing the National Assessment as an educational evaluation tool. The problems faced by partners are limited understanding of the concept of National Assessment and technical skills in managing instruments, analyzing data, and following up on assessment results. The methods used in this activity are participatory-based socialization and technical training involving teachers as active participants. Activities are carried out through material delivery, interactive discussions, and hands-on practice using assessment tools. The results of the activity showed an increase in teachers' knowledge and skills in understanding the National Assessment indicators, developing learning strategies in line with the Pancasila learner profile, and optimizing the use of assessment results to improve the quality of learning in the classroom. Thus, this PKM activity contributed to improving the quality of learning at Rara Elementary School while supporting the achievement of national education standards.